Facility and Family Communication during the COVID-19 Visit Restriction: Early Perspectives of Family Members. Issue 8 (17th November 2021) - Straker, Jane K; Choi, Mi Sun
ABSTRACT: During the COVID-19 pandemic, family concerns regarding residents in long-term care facilities (LTCFs) increased due to a high proportion of COVID cases and deaths among residents and restrictions that made it impossible to visit. These changes created numerous challenges for facilities communicating with families, and between families and residents. However, little is known about how these facilities addressed these communication challenges and how those communication strategies were related to family perceptions about the facility. We implemented an online survey of family members or friends of residents in LTCFs from April 28 to June 19, 2020, using convenience sampling. A total of 174 responses nationwide reported the types of communications used, frequency of communication and alternative visits, and whether respondents had peace of mind, would recommend the facility, or were considering removing the resident from the facility. The results of our hierarchical logistic regression showed that respondents felt greater peace of mind when there were multiple communication channels to contact the resident. Also, respondents had more negative perceptions of a facility when they were not informed about confirmed COVID cases. Our findings suggest multiple communication channels and transparency about COVID status were effective in keeping positive family perceptions about the facility.